The Rational Ignorance as Illustrated on Mushanokoji Saneatsu’s Daruma - Listyaningsih Listyaningsih; Siti Wulandari; Rommel Utungga Pasopati (KIRYOKU, 2023)
As reflection of everyday life, literature highlights matters from simple dialogues to spiritual understandings. It is on point with Mushanokoji Saneatsu’s literary work in 1962 named Daruma that is full of metaphysical meanings. The main character seems to ignore anything else to reach such enlightenment. Interestingly, it shows that being ignorance actually makes sense. The idea is also in line with model of rational ignorance underlined by Bryan Caplan in which political and economic ideas are asserted. Then, how is rational ignorance illustrated on Mushanokoji Saneatsu’s Daruma? Through qualitative method on cultural studies, this paper exposes the search of enlightenment is matter of going out from caring too much to surroundings. Ignorance is not abandoning things at all. It is such choice to focus on a thing even if the doer must sacrifice other aspects. The main idea is following rational mind while postponing other known phenomena. In conclusion, by underlining situation of being ignorant, Saneatsu would like to examine that reaching such enlightened self is matter of being both spiritual and rational as well.